Epidemiology of fatal and hospitalised injuries among youth in Fiji (TRIP 15). (27th August 2016) - Herman, Josephine; Peiris‐John, Roshini; Wainiqolo, Iris; Kafoa, Berlin; Laginikoro, Paul; McCaig, Eddie; Ameratunga, Shanthi
Abstract : Aim: To determine the burden and characteristics of fatal and hospitalised injuries among youth in Fiji. Methods: We conducted a cross‐sectional analysis of the Fiji Injury Surveillance in Hospitals database – a prospective population‐based trauma registry – to examine the incidence and epidemiological characteristics associated with injury‐related deaths and hospital admissions among youth aged 15–24 years. The study base was Viti Levu, Fiji, during the 12‐month period concluding on 30 September 2006. Results: One in four injuries in the Fiji Injury Surveillance in Hospitals database occurred among youth ( n = 515, incidence rate 400/100 000). Injury rates were higher among men, those aged 20–24 years compared with 15‐ to 19‐year‐olds, and indigenous Fijians (iTaukei) compared with Indians. The leading causes among indigenous Fijians were being hit by a person/object (men) and falls (women), whereas for Indians, it was road traffic injuries (men) and intentional poisoning (women). Most injuries occurred at home (39%) or on the road (22%). Of the 63 fatal events, 57% were intentional injuries, and most deaths (73%) occurred prior to hospitalisation. Homicide rates were four times higher among indigenous Fijians than Indians, whereas suicide rates were five times higher among Indians compared with indigenous Fijians. Conclusions: Important ethnic‐specific differences in the epidemiology of fatal and serious non‐fatal injuries are apparent among youth in Fiji. Efforts to prevent the avoidable burden of injury among Fiji youth thus requires inter‐sectoral cooperation that takes account of important sociocultural, environmental and health system factors such as unmet mental healthcare needs and effective pre‐hospital trauma services.